Expression pattern of Stlhcb gene family in potato and effects of overexpression of Stcp24 gene on potato photosynthesis - Tang, Xinhua; Liu, Yulin; Li, Shiwei; Pei, Yating; Wei, Qiaorong; Zhang, Lili; Shi, Ying (PloS one, 2024)
Potato is one of the four staple food crops in the world. It has a wide range of cultivation, high yield, and high nutritional value. Enhancing the photosynthesis of potato is particularly important as it leads to an increase in the potato yield. The light-harvesting pigment-binding protein complex is very important for plant photosynthesis. We identified 12 Stlhcb gene family members from the potato variety "Atlantic" using transcriptome sequencing and bioinformatics. The proteins encoded by the Stlhcb gene family have between 3358 and 4852 atomic number, a relative molecular weight between 24060.16 and 34624.54 Da, and an isoelectric point between 4.99 and 8.65. The RT-qPCR results showed that the 12 Stlhcb genes were expressed in a tissue-specific and time-dependent fashion under low light. The relative expression of the Stlhcb genes in the leaves was significantly higher than that in the stems and roots, and the relative expression of these genes first increased and then decreased with the prolongation of light exposure time. The Stcp24 gene with the highest expression was cloned, and an expression vector was constructed. A subcellular localization analysis was performed in tobacco and an overexpression experiment was performed in potato using an Agrobacterium-mediated method. The subcellular localization analysis showed that the protein encoded by Stcp24 was located in chloroplasts as expected. Overexpression of Stcp24 in transgenic potato increased the yield of potatoes and the content of chlorophyll a and b; increased the net photosynthetic rate, transpiration rate, stomatal conductance, electron transport efficiency, and semi-saturated light intensity; and promoted photosynthesis and plant growth. This study provides a reference for the study of the function of the potato light-harvesting pigment-binding protein gene family. It lays a foundation for further study of the mechanism of the photosynthesis of potato, improvement of the light energy utilization of potato, and molecular breeding of potato.